Low Molecular Weight Fucoidan against Renal Ischemia–Reperfusion Injury via Inhibition of the MAPK Signaling Pathway - Chen, Jihui (Public Library of Science, 2013)
BACKGROUND: Ischemia reperfusion injury (IRI) is a leading cause of acute kidney injury (AKI) in both native and transplanted kidneys. The objective of the present study was to evaluate whether low-molecular-weight fucoidan (LMWF) could attenuate renal IRI in an animal model and in vitro cell models and study the mechanisms in which LMWF protected from IRI. METHODOLOGY/PRINCIPAL FINDINGS: Male mice were subjected to right renal ischemia for 30 min and reperfusion for 24 h, or to a sham operation with left kidney removed. Kidneys undergone IR showed characteristic morphological changes, such as tubular dilatation, and brush border loss. However, LMWF significantly corrected the renal dysfunction and the abnormal levels of MPO, MDA and SOD induced by IR. LMWF also inhibited the activation of MAPK pathways, which consequently resulted in a significant decrease in the release of cytochrome c from mitochondria, ratios of Bax/Bcl-2 and cleaved caspase-3/caspase-3, and phosphorylation of p53. LMWF alleviated hypoxia-reoxygenation or CoCl(2) induced cell viability loss and ΔΨm dissipation in HK2 renal tubular epithelial cells, which indicates LMWF may result in an inhibition of the apoptosis pathway through reducing activity of MAPK pathways in a dose-dependent manner. CONCLUSIONS/SIGNIFICANCE: Our in vivo and in vitro studies show that LMWF ameliorates acute renal IRI via inhibiting MAPK signaling pathways. The data provide evidence that LMWF may serve as a potential therapeutic agent for acute renal IRI.